2006
DOI: 10.1159/000093586
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness, Safety and Cost-Effectiveness of Homeopathy in General Practice – Summarized Health Technology Assessment

Abstract: Introduction: The Health Technology Assessment report on effectiveness, cost-effectiveness and appropriateness of homeopathy was compiled on behalf of the Swiss Federal Office for Public Health (BAG) within the framework of the ‘Program of Evaluation of Complementary Medicine (PEK)’. Materials and Methods: Databases accessible by Internet were systematically searched, complemented by manual search and contacts with experts, and evaluated according to internal and external validity criteria. Results: Many high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 68 publications
(55 reference statements)
0
48
0
6
Order By: Relevance
“…16 The use of CAM in Switzerland, its efficacy, appropriateness, and cost-effectiveness have been evaluated within the frames of a federal program (Complementary Medicine Evaluation Program, PEK), which revealed that CAM was associated with a higher patient satisfaction, weaker=less frequent side-effects, and lower costs than conventional medicine (CM). 15,[17][18][19][20] The use of CAM by children in Switzerland has just started to be unveiled. A previous study performed at the intensive care unit of the Children's Hospital of Zurich revealed that 18% of the parents of critically ill pediatric patients applied some form of CAM.…”
Section: Introductionmentioning
confidence: 99%
“…16 The use of CAM in Switzerland, its efficacy, appropriateness, and cost-effectiveness have been evaluated within the frames of a federal program (Complementary Medicine Evaluation Program, PEK), which revealed that CAM was associated with a higher patient satisfaction, weaker=less frequent side-effects, and lower costs than conventional medicine (CM). 15,[17][18][19][20] The use of CAM by children in Switzerland has just started to be unveiled. A previous study performed at the intensive care unit of the Children's Hospital of Zurich revealed that 18% of the parents of critically ill pediatric patients applied some form of CAM.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies present data that homeopathic remedies are not operating though a placebo response. Several reports, for example, show that homeopathic remedies are effective in treating infants, comatose patients and animals [7][8][9][10][11][12][13] induce oestrus in cows [14]. Another report has shown that homeopathic remedies might be trigger cytolytic activity in breast cancer cells maintained in culture [15].…”
Section: Ethical and Regulatory Issues Regarding Homeopathymentioning
confidence: 99%
“…External validity, on the other hand, addresses the generalizability of anobservedeffectforthelargerpopulationfromwhomthe study participants were drawn; and model validity relates to the concordance between the study design and an idealized setting(formoredetails,see [1,5]). Forexternalandmodel validity in studies, WS-CAM practitioners would need to (a)useindivisible,interdependent,iterativepackagesofcare rather than isolated standardized elements of a package; (b) ensure that practitioners involved in studies are well trained and highly experienced; (c) treat real-world patients withconfoundingco-morbidconditions,psychosocialfactors, and other treatments; and (d) evaluate complex, emergent patient-wide outcomes in each case, rather than the simple organ-ordisease-specificeffects.ThemajorfeaturesofWSCAMincludecoordinated,adaptive,andindivisiblepackages ofcareandemergentpositivepatient-wideoutcomesinboth globalfunction(e.g.,qualityoflife)andmultiplelocalsubsystems(e.g.,'non-specific'changesinmanysymptoms,notjust the original chief complaint).…”
Section: Introductionmentioning
confidence: 99%